AI IN 2024 UIN INFORMATION SYSTEMS EDUCATION: ACADEMIC IMPACTS AND ETHICAL CHALLENGES - Muhammad Thoriq Nabasa; Nurmiati , Evy; Bayu Khayatullah, Muhamad (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The penetration of Artificial Intelligence (AI) in academic environments has sparked a dual reality, balancing learning innovation against the disruption of integrity. This study investigates the practical impacts and ethical implications of AI adoption among the 2024 Information Systems cohort at the Faculty of Science and Technology, UIN Syarif Hidayatullah Jakarta. Utilizing a mixed-methods approach that integrates a macro-level Systematic Literature Review (SLR) with local quantitative surveys, the research uncovers a sharp contrast. Practically, 100% of respondents indicated that AI effectively breaks down complex concepts for better understanding , while also significantly accelerating the completion of academic tasks. However, the literature review highlights an alarming moral shift known as the AI-Human Unethicality Gap, where 61% of students in collectivist cultures tend to rationalize plagiarism when using AI tools. This situation is exacerbated by a regulatory void, with 74% of higher education institutions in developing countries lacking explicit AI guidelines. The study concludes that reactive bans are not a viable solution; instead, universities must proactively integrate a Digital Ethics Literacy curriculum and implement next-generation plagiarism detection systems based on Natural Language Processing (NLP) to uphold the dignity of scientific honesty.